'En Australie, je parle une langue minoritaire': Catherine Rey's Une femme en marche as Australian Life Writing in French. Issue 4 (2nd October 2017) - Edwards, Natalie
ABSTRACT: In the Asia-Pacific region, literature is plurilingual. Even Australian literature is not necessarily written in English. There are several contemporary Australian authors who write in languages other than English and many who write in various English es . This article examines one such example by analysing the life writing of Catherine Rey. It focuses upon the self-reinvention that this French author performed by migrating to Australia in mid-life. Focusing on the first-person narrative Une femme en marche (2007) and drawing comparisons with self-reflexive essays by this author, the article teases out the contrasts between Rey's representation of France and Australia as spaces for literary creation. It then interrogates how Rey reinvents herself through linguistic play within her life writing. Using theories of 'translanguaging', the article analyses the ways in which this author blends French and English to probe the gaps in languages, to nuance literary representation and to create new linguistic forms to express her self-narrative.